Corrigendum to “The analytical evaluation threshold for inorganic metal extractables and leachables analysis of medical devices” [Regulat. Toxicol. Pharmacol. 154 (2024), 105725] - Chad P. Satori; Catherine D. Christensen; Stephanie M. Street; Mikaelle Giffin; Christopher M. Pohl; Whitney V. Christian (Regulatory Toxicology and Pharmacology, 2025)

Calcium isotopes support spatial redox gradients on the Tethys European margin across the Triassic-Jurassic boundary - Ashley N. Prow-Fleischer; Zunli Lu; Clara L. Blättler; Tianchen He; Pulkit Singh; Preston Cosslett Kemeny; Jordan P. Todes; Alexandre Pohl; Tripti Bhattacharya; Bas van de Schootbrugge; Paul B. Wignall; Simona Todaro; et al. (Chemical Geology, 2025)

An Ordovician Assemblage of Cool Water‐Adapted Paleotropical Ostracods Suggests an Early Psychrosphere - Anna McGairy; Phong Duc Nguyen; Mark Williams; Christopher P. Stocker; Thomas H. P. Harvey; Toshifumi Komatsu; Thomas W. Wong Hearing; C. Giles Miller; Chloé M. Marcilly; Alexandre Pohl (Island Arc, 2025)
An ostracod assemblage from the Late Ordovician (Katian) Phu Ngu Formation of northern Vietnam, South China paleoplate, yields typical Baltic and Laurentian‐affinity genera together with some endemic forms. Detailed paleontological and sedimentary analysis of the Phu Ngu Formation suggests it was deposited in a deeper marine forearc setting, below storm wave base, but with (at least intermittently) oxygenated sea‐bottom conditions. Taphonomic assessment of the ostracod assemblage suggests it is in situ. The occurrence of globally widespread ostracod genera, including those from paleocontinents that were geographically remote from South China, is difficult to reconcile with the assumed limited dispersal capability of ostracods in shallow‐shelf settings—a characteristic that has often been used to refine Ordovician paleogeographical reconstructions. Here, we present the novel approach of using paleoclimate reconstructions to assess the environmental distributions of Paleozoic ostracod genera. We show that the deep‐marine depositional setting of our documented assemblage, together with general circulation model simulations of Ordovician ocean‐temperatures, suggests an early radiation of benthic ostracods into the deeper, colder, and thermally uniform ocean below the thermocline. The presence of a globally‐distributed psychrospheric (cool and deep marine) ostracod fauna would imply that our understanding of Ordovician ostracod dispersal is incomplete, and future paleobiogeographical studies should try to decouple the signal of shallow‐shelf benthic taxa, often endemic and probably limited by sea temperature, from those that are more cosmopolitan and tolerant of cooler, deeper waters.

A new type of submarine chimneys built of halite - C. Siebert; D. Ionescu; U. Mallast; S. Merchel; B. Merkel; P. Möller; S. Pavetich; T. Pohl; T. Rödiger; Y. Yechieli (Science of The Total Environment, 2024)

The analytical evaluation threshold for inorganic metal extractables and leachables analysis of medical devices - Chad P. Satori; Catherine D. Christensen; Stephanie M. Street; Mikaelle Giffin; Christopher M. Pohl; Whitney V. Christian (Regulatory Toxicology and Pharmacology, 2024)

Digitalization and Sustainability: A Call for a Digital Green Deal - T. Santarius; L. Dencik; T. Diez; H. Ferreboeuf; P. Jankowski; S. Hankey; A. Hilbeck; L.M. Hilty; M. Höjer; D. Kleine; S. Lange; J. Pohl; et al. (Environmental Science & Policy, 2023)

Pheromone-enhanced lure blends and multiple trap heights improve detection of bark and wood-boring beetles potentially moved in solid wood packaging - L. Flaherty; J. M. G. Gutowski; C. Hughes; P. Mayo; T. Mokrzycki; G. Pohl; P. Silk; K. Van Rooyen; J. Sweeney (Journal of Pest Science, 2019)

The mediating role of cortical thickness and gray matter volume on sleep slow-wave activity during adolescence - Aimée Goldstone; Adrian R. Willoughby; Massimiliano de Zambotti; Peter L. Franzen; Dongjin Kwon; Kilian M. Pohl; Adolf Pfefferbaum; Edith V. Sullivan; Eva M. Müller-Oehring; Devin E. Prouty; Brant P. Hasler; Duncan B. Clark; et al. (Brain Structure and Function, 2018)

A complete chitinolytic system in the atherinopsid pike silverside Chirostoma estor : gene expression and activities - P. Pohls; L. González‐Dávalos; O. Mora; A. Shimada; A. Varela‐Echavarria; E. M. Toledo‐Cuevas; C. A. Martínez‐Palacios (Journal of Fish Biology, 2016)
The expression and digestive activity of pike silverside Chirostoma estor endogenous chitinases were analysed in samples from four life stages: whole eggs; larvae; juvenile intestine and hepatopancreas and adult intestine and hepatopancreas. A chitinase cDNA was cloned and partially sequenced ( GenBank accession number: FJ785521 ). It was highly homologous to non‐acidic chitinase sequences from other fish species, suggesting that it is a chitotriosidase. Quantitative PCR showed that this chitinase was expressed throughout the life span of C. estor , with maximum expression in the hepatopancreas of juveniles. Chitotriosidase and chitobiosidase activities were found at all life stages, along with a very high level of N ‐acetyl glucosaminidase ( NAGase ). The chitotriosidase activity could be encoded by the cloned complementary (c) DNA , although additional chitinase genes may be present. The chitotriosidase activity appeared to be transcriptionally regulated only at the juvenile stage. The expression and activity of chitinases tended to increase from the early to juvenile stages, suggesting that these variables are stimulated by chitin‐rich live food. Nevertheless, the feeding of juvenile and adult fish with both live food and a balanced commercial diet seemed to provoke significant reductions in pancreatic NAGase secretion and/or synthesis in the gut. Moreover, all chitinase activities were lower in adults, probably reflecting a higher intake and use of the balanced diet. The observation of chitotriosidase and chitobiosidase activities together with a very high NAGase activity suggest the presence of a complete and compensatory chitinolytic chitinase system that enables this stomachless short‐gut fish species to use chitin as an energy substrate. These novel findings suggest that dietary inclusions of chitin‐rich ingredients or by‐products might reduce the farming costs of C. estor without impairing performance.

Coastal oceanic climate change and variability from 1982 to 2009 around South Africa - M Rouault; B Pohl; P Penven (African Journal of Marine Science, 2010)

Acetylsalicylic acid as antifungal in Eremothecium and other yeasts - N. J. Leeuw; C. W. Swart; D. M. Ncango; C. H. Pohl; O. M. Sebolai; C. J. Strauss; P. J. Botes; P. W. J. van Wyk; S. Nigam; J. L. F. Kock (Antonie van Leeuwenhoek, 2007)

Acetate-enhanced polymerized triacylglycerol utilization by Mucor circinelloides - M. Joseph; J. L. F. Kock; C. H. Pohl; P. J. Botes; E. van Heerden; A. Hugo (World Journal of Microbiology and Biotechnology, 2005)

Uncovering the first double brimmed hat-shaped ascospores in Ambrosiozyma platypodis Van der Walt - A. S. Bareetseng; J. L. F. Kock; C. H. Pohl; E. E. Pretorius; P. W. J. Van. Wyk (Antonie van Leeuwenhoek, 2005)

Bioprospecting for novel hydroxyoxylipins in fungi: presence of 3-hydroxy palmitic acid in Saccharomycopsis malanga - O. Sebolai; J.L.F. Kock; C.H. Pohl; D.P. Smith; P. J. Botes; E.E. Pretorius; P.W.J. Van Wyk; S. Nigam (Antonie van Leeuwenhoek, 2001)

A novel oxylipin-associated ‘ghosting’ phenomenon in yeast flocculation - J.L.F. Kock; P. Venter; D.P. Smith; P.W.J. Van Wyk; P.J. Botes; D.J. Coetzee; C.H. Pohl; A. Botha; K-H. Riedel; S. Nigam (Antonie van Leeuwenhoek, 2000)

Impaired direction and extent specification of aimed arm movements in humans with stroke-related brain damage - M. R. Velicki; C. J. Winstein; P. S. Pohl (Experimental Brain Research, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Exopolysaccharide production by cyanobacteria grown in closed photobioreactors and immobilized using white cotton towelling - D. Fischer; U.G. Schlösser; P. Pohl (Journal of Applied Phycology, 1997)